A study of housing development on mining area / Siti Nor Ain Mohamad - Mohamad, Siti Nor Ain (Faculty of Architecture, Planning and Surveying, 2013)
Mining land is a land that has being used for mining activity. Kinta Valley is one of the major areas that involved on the activity. Due to the lack of virgin land on that area, mining land has being used for development. The increases of population in Ipoh also the main factors that contribute to the uses of former mining land for housing development. This study consists of seven chapters that discuses about housing development on mining land. It is discussed to ensure the mining land is suitable for housing developement. Case study selected is in Taman Pengkalan Utama, Taman Pengkalan Tiara and Desa Pengakalan Bandaraya which is located in Ipoh thus under the Kinta Valley area. The analysis of data collected from structured interview and questionnaire have been fulfill the objectives of this study. As a conclusion, it prove that the mining land is suitable to be developed for housing development.